Analisis Pemahaman Konsep dan Implementasi Keterampilan Dasar Mengajar Mahasiswa PGSD - Maharbid, Dian; Amelia, Decenni; Maulidah, Neni (Jurnal Elementaria Edukasia, 2023)
This study aims to analyze and describe the basic teaching skills of elementary school teacher candidates when carrying out teaching practice activities in microteaching courses. Instruments in this research include; questionnaire, work reports, and documentation. The research subjects were 74 people of 5th-semester PGSD students at Bhayangkara University, Jakarta Raya. The results showed that the conceptual understanding indicator of PGSD students obtained high categori (72.07%). Meanwhile, for each concept of basic teaching skills average was 81.08% sorted into a very high category. Students are split into some groups according to basic skills and implement these skills in microteaching activities. The results of observing the implementation of basic teaching skills analyzed for each skill obtained the skill of opening and closing by 69% of students going well. Explanation skills (75%), variations skills (66%), questioning skills (74%), reinforcement skills (63%), and small group and individual teaching skills 71% sorted into the good category. Meanwhile, the skills of managing a class (50%) and guiding small group discussions (53%) were sorted into the fairly good category. In conclusion, with an average gain of 65.13%, the basic teaching skills can be implemented properly sorted in the good category.